FAKTOR-FAKTOR YANG MEMPENGARUHI PENJUALAN BUMBU MASAK GUNUNG SALJU DI KECAMATAN MUTIARA KABUPATEN PIDIE - Mujiburrahmad Muji (Jurnal Agrisep, 2016)
Price is one of the most important factors that determines success of a company. It is crucial because the company should set up the price for products to calculate the magnitude of profit that the company receives. To determine the price of a kitchen recipe that is produced in Mutiara Subdistrict, it is necessary to analyze the factors that greatly influence the sale of the product. Therefore, the objective of this research is to analyze several factors that influence the sale of Gunung Salju kitchen recipe in Mutiara Subdistrict Pidie Regency. The research is conducted in Mutiara Subdistrict Pidie Regency. Purposive method is used to determine the research location with consideration that such location is one of the locations that produces and sells the kitchen recipe of Gunung Salju in Mutiara Subdistrict. The objects of this research is that the consumers that consume the product. Non Probability Sampling method, where every member in a population does not have the same probability to be a sample, is used as a method to collect the research sample. In this research, population is those who buy and consume one of the kitchen recipes produced by Gunung Salju. Then, we take 50 people that represent the population to be the sample. The result shows that price, quality and selling location significantly influence the sale of Gunung Salju kitchen recipe in Mutiara Subdistrict Pidie Regency. The F value is greater than F table. Therefore, the independent variables significantly influence the dependent variable.